2020
DOI: 10.1111/nyas.14379
|View full text |Cite
|
Sign up to set email alerts
|

The SARS‐CoV‐2/COVID‐19 pandemic and challenges in stroke care in India

Abstract: Stroke care in India has evolved rapidly in the last decade with a focus on stroke awareness, prevention, rapid triage, treatment, and rehabilitation. But acute stroke care and poststroke rehabilitation in the country have limitations owing to the economic constraints and poor access to health care. The SARS-CoV-2/COVID-19 pandemic has made stroke care even more challenging. We outline the unfavorable circumstances in stroke care induced by the pandemic; propose mitigating measures; crisis management; and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…Furthermore, a higher frequency of stroke with unknown etiology was seen during the lockdown (50%), compared with the same period in 2019 (10%). A survey of 13 comprehensive stroke centers in India that was conducted by Sylaja et al [ 138 ] revealed 61%, 64.76%, and 67.21% reduction in the number of stroke admissions, in intravenous thrombolysis, and in neuroendovascular procedures, respectively.…”
Section: Cns Manifestations Associated With Covid-19mentioning
confidence: 99%
“…Furthermore, a higher frequency of stroke with unknown etiology was seen during the lockdown (50%), compared with the same period in 2019 (10%). A survey of 13 comprehensive stroke centers in India that was conducted by Sylaja et al [ 138 ] revealed 61%, 64.76%, and 67.21% reduction in the number of stroke admissions, in intravenous thrombolysis, and in neuroendovascular procedures, respectively.…”
Section: Cns Manifestations Associated With Covid-19mentioning
confidence: 99%
“…During the pandemic, one major negative impact on acute care for stroke was the decline in emergency hospital admissions, consistent with reports in different regions in China or other countries. The degree of reduction varied from 10 to 70% ( 11 , 13 , 13 , 16 19 , 26 – 31 ). One recent report in China also reported a 40% reduction in stroke hospital admissions ( 16 ), similar to our results (45.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these efforts, acute stroke care is still negatively impacted (11)(12)(13)(14)(15). Reductions of 10-70% in stroke hospital admission are reported in several countries (13,(16)(17)(18)(19), though COVID-19 may probably increase the risk of ischemic stroke as a result of endothelial injury and hypercoagulable status and other impacts on the central nervous system (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 disease is caused by a novel coronavirus (SARS-COV-2) that emerged in the Wuhan province of china [ 1 , 2 ]. The first documented human infection was reported in Dec 2019 and since then, the disease has spread at an unprecedented speed and magnitude to become the greatest healthcare concern of the twenty-first century [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%